Fazlur Rahman's Thoughts on Islamic Education Reform and Its Significance for the Education System in Indonesia - Rasalhaque Daffa Taruna; Eva Dewi; Husaini Nasution (Bulletin of Indonesian Islamic Studies, 2025)
Islamic education plays a vital role in shaping the personality and civilization of its adherents; however, it is currently grappling with an epistemological and methodological crisis that creates a divide between religious knowledge and general knowledge. Rigid and non-contextual educational approaches further contribute to the stagnation of the Islamic education system. This study adopts a qualitative approach, utilizing a literature review method to gather and analyze both primary and secondary sources related to human freedom from the perspective of Islamic education. A descriptive analytical method is employed both deductively and inductively to achieve a deeper understanding of the topic. The focus of the study is on Fazlur Rahman's ideas concerning the integration of knowledge, curriculum reform, and the transformation of teaching methodologies. Rahman argues for an Islamic education that transcends mere rituals, promoting critical thinking, creativity, and social engagement. He advocates for the integration of *tarbiyah* (moral education) and *ta'lim* (the teaching of knowledge), alongside enhancing teacher capacity and proficiency in foreign languages to expand access to knowledge. Rahman's concepts align well with the principles of the 2013 Curriculum, which emphasizes thematic, integrative, and student-centered learning. This article offers a conceptual framework based on Rahman's insights as a viable solution to the epistemological crisis and serves as a reference for the development of integrative, contextual, and adaptive Islamic education.